Las horas complementarias en la recuperación pedagógica en el área de lengua y literatura, en los estudiantes del cuarto año de educación básica de la unidad educativa “13 de Abril”, del cantón Ventanas, provincia de Los Ríos, durante el periodo lectivo 2011-2012 - Chévez Vera, Jadira Mercedes (2012)
The complementary hours in the pedagogic recovery in the language area and literature for the students of fourth grade in Elementary School, it gathers our opinions as well as the theories of different authors of texts and comments on web sites, validating the application of the Complementary Hours for Pedagogic Recovery established in the Constitution of Ecuador and the Organic law of Intercultural Education. Being several articles of these laws the foundation to support our investigation. Chapter I of the theoretical framework is framed this to scientifically demonstrate the probability of the effectiveness and application of the complementary hours of pedagogic recovery, gathering the articles of the constitution and the LOEI that establish the obligatory application in the new Ecuadorian educational system and to validate its application due to the current Ecuadorian educational reality, and to confront it with realities of other countries and with certain authors' theories that stand out and focus certain aspects of the teaching and learning that condition the motivation and the grade of the students' receptivity, consolidating the fact that not alone we need to compete in a global environment and universalized in the education, but rather it is also to prepare our children so that they can confront the challenges of this society and to contribute to the productive development of the society. In the chapter II are focused type, form, time and place where this investigation was carry out; the methods are detailed this way, technical and applied instruments to the group or universe of investigation in the established dimension. In the analysis and interpretation of data corresponding to chapter III, graphics were tabulated, and analyzed each question of the educators´ surveys, students and parents making a correlation among them, carrying out the same procedure for the questions of the diagnose test and of recovery, tabulating and analyzing the answers for each question of both tests in one graphic, to stand out, to compare and to analyze in a better way the effectiveness of the application of the complementary hours of pedagogic recovery in the language area and literature. Likewise, in the confirmation of the hypothesis, the systematic steps are detailed which were made of each process to approach to the truthfulness of the confirmation. Finally in chapter IV the proposal of the investigation work was made, not like an absolute solution, but like an effective demonstration of the application of the complementary hours of pedagogic recovery and of the advantages in the students of receiving them, fomenting and informing to the whole educational community of the agreement and mutual commitment to accomplish and to make it accomplished, of being supervisors and participants of the application and the educational change in improvements of the Ecuadorian education.